Organizing a Health Camp: Management Perspective - Gajuryal, Sharad Hari; Gautam, Sandhya; Satyal, Narayan; Pant, Basant (Nepalese Medical Journal, 2019)
Health camps or outreach clinics are the effective strategies adopted by both government and non-government organizations, associations, and societies with various interests and scope. A well-organized health camp with a concentration on the various principles of planning, coordination, collaboration, tools, and techniques will not only make the health camp successful but also aids in improving the health status of the unreached community who are often deprived of basic to advance health care facility due to different circumstances.